1997
DOI: 10.1177/026988119701100406
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and the common cold

Abstract: An experiment was carried out to determine whether caffeinated and decaffeinated coffee removed the malaise (reduced alertness, slower psychomotor performance) associated with having a common cold. One hundred volunteers were tested when healthy and 46 returned to the laboratory when they developed colds. Those subjects who remained healthy were then recalled as a control group. On the second visit subjects carried out two sessions, one pre-drink and another an hour after the drink. Subjects were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…16 Indeed, ingestion of caffeine, which increases alertness, has been shown to remove the cold-induced performance impairments seen in laboratory tasks. 17 This suggests that a further study examining whether caffeine can remove the effects found here is required. Similarly, it will be important to determine whether medications aimed at producing symptomatic relief also remove the behavioural problems associated with the common cold.…”
Section: Discussionmentioning
confidence: 94%
“…16 Indeed, ingestion of caffeine, which increases alertness, has been shown to remove the cold-induced performance impairments seen in laboratory tasks. 17 This suggests that a further study examining whether caffeine can remove the effects found here is required. Similarly, it will be important to determine whether medications aimed at producing symptomatic relief also remove the behavioural problems associated with the common cold.…”
Section: Discussionmentioning
confidence: 94%
“…It was predicted on the basis of our previous research, and the findings of other researchers, that caffeine would increase alertness (Smith et al 1993;Warburton 1995;Brice and Smith 2001a), increase anxiety (Loke 1988;, reduce simple reaction time (Clubley et al 1979;Smith et al 1994;Smith et al 1997) and improve sustained attention (Smith et al 1992;Brice and Smith 2001b), dual-task performance (Kerr et al 1991) and the encoding of new information (Smith AP et al 1999). The aim of the present study was to determine whether these effects would be observed with both administration of multiple small doses and a single large dose of caffeine.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, caffeine can remove the impaired performance and negative mood associated with the common cold [94] and attenuate memory impairment induced by scopolamine in humans [95]. In general, effects of small doses of caffeine are detected in low alertness paradigms, whereas more global and positive effects can be observed with doses of 200-300 mg (1,53,96).…”
Section: S243mentioning
confidence: 99%